(untitled) (Cardiovascular Journal, 2020)
An echocardiographic investigation is one of the key modalities of diagnosis in patients suffering from COVID 19, especially if they are elderly, have associated comorbid conditions, and pregnant. Hence, it is becoming extremely essential to look into the correct safety precautions, health-care professionals must take while conducting an echo investigation. At the same time, a focused echo examination aimed at correct imaging view acquisition in the shortest possible time is the need of the hour. The decision matrix formulated for conducting an echocardiographic evaluation is based on the presence or absence of cardiological comorbidity vis-a-vis positive or suspected for COVID- 19. The safety measures and image acquisition have been constructed keeping in mind the current safety precautions by the World Health Organization, the Centers for Disease Control and Prevention, and the Ministry of Health and Family Welfare, India. Cardiovasc. j. 2020; 13(1): 97-101